Urgencias pediátricas atendidas en una consulta de atención primaria (I): análisis de la demanda - Fernández Cano, G. (Aten Primaria, 2000)
OBJECTIVES: To study paediatric emergencies in a primary care clinic, evaluating how suitable it is and the factors underlying the emergencies. DESIGN: A prospective, longitudinal study during the working days of alternate weeks between July 1 1996 and June 30 1997. SETTING: Urban paediatrics clinic, on the afternoon shift (2 to 9 p.m.), of the Vicente Soldevilla Primary Care Team (PCT) in Vallecas (Madrid). PARTICIPANTS: Population registered with the PCT: 2890 children between 0 and 14. RESULTS: 723 emergencies were attended (consultations without prior appointment), which represented 21.1% of all non-scheduled consultations. The mean was 5.8 ± 2.8 emergencies per day (range 0-13). They were more common on Mondays (6.8 ± 2.4), in October (8.2 ± 1.6) and in Autumn (5.8 ± 2.6). 95% were of children registered with the PCT. Maximum attendance was between 4 p.m. and 7 p.m. (59%), coinciding with the on-demand clinic. 6.9% of the emergencies were unjustified, 51.3% were justified, and 41.8% could have asked for an appointment beforehand. The main reasons for attending as an emergency were: the symptoms beginning after the appointments desk had closed (43.2%), convenience (16.7%) and importance of the illness (12.4%). CONCLUSIONS: Emergencies make up a large proportion of consultations, and distort the organisation of the day’s activities. 41.8% of cases could have requested a prior appointment. It is striking that 16.7% said they attended as an emergency for convenience. Children under 6 were those who attended emergencies most.